The empty science lab : solve your way out! : use your science skills to escape! - Wood, Kevin (New York, NY : Gareth Stevens Publishing, 2023)
An unlocked door to a secret science lab would be hard for any student to ignore! But what if you snuck in--and the door locked behind you? In this book, readers need to solve puzzles and find codes throughout the pictures and text in order to escape! Science terms and concepts, such as animal classification, the human body, and the pH scale, are described as part of the story.
A STEAM interactive puzzle book --Front cover.
5.0
3-6
Keywords: Science -- Juvenile literature; Puzzles; Science; Puzzles; Puzzles and games; Creative nonfiction; Escape room games. -- Juvenile literature; STEAM